PHELAN–MCDERMID SYNDROM (del 22q13 AND r(22)): LITERATURE REVIEW AND 2 CASE REPORTS - M. Yu. Bobylova; M. A. Nikitina; K. Yu. Mukhin; A. V. Kulikov (Русский журнал детской неврологии, 2017)
Phelan–McDermid syndrome (PMS) is a microdeletion syndrome associated with the loss of terminal segments in chromosome 22, sometimes with development of the ring chromosome 22. Clinical manifestations of PMS include epilepsy and mental disorders (autism, mental deficiency, lack of expressive speech, sleep disorders, mood disorders since adolescence). Neurologic status is characterized by diffuse muscle hypotonia since birth, delayed development of motor skills, functional gastrointestinal disorder. Children over 1 year develop autism spectrum disorders; they have a specific awkward gait with frequent falls and decreased sensitivity to pain. Severe delay in the development of verbal intelligence (when expressive speech is absent or represented by individual words) are typical for these patients. Epileptiform activity appearing in a form of benign epileptiform discharges of childhood is usually diagnosed in all PMS patients; epileptic seizures are documented in half of the cases. The disease is characterized by secondarily generalized, age-related epileptic seizures with oral-pharyngeal manifestations. In some cases epilepsy becomes drug-resistant. Current article describes 2 clinical cases of PMS.